Which patients received a ReSPECT form, what was documented and what were the patient outcomes? A protocol for a retrospective observational study investigating the impact of the COVID-19 pandemic on the implementation of the ReSPECT process - Lucy Selman; Charlotte Chamberlain; Adam McDermott; Claire A Woodall; Lucy Victoria Pocock (BMJ Open)
Introduction Recommended Summary Plan for Emergency Care and Treatment (ReSPECT) is a UK advance care planning (ACP) initiative aiming to standardise the process of creating personalised recommendations for a person’s clinical care in a future emergency and therefore improve person-focused care. Implementation of the ReSPECT process across a large geographical area, involving both community and secondary care, has not previously been studied. In particular, it not known whether such implementation is associated with any change in outcomes for those patients with a ReSPECT form.Implementation of ReSPECT in the Bristol, North Somerset and South Gloucestershire (BNSSG) Clinical Commissioning Group (CCG) area overlapped with the first UK COVID-19 wave. It is unclear what impact the pandemic had on the implementation of ReSPECT and if this affected the type of patients who underwent the ReSPECT process, such as those with specific diagnoses or living in care homes. Patterns of clinical recommendations documented on ReSPECT forms during the first year of its implementation may also have changed, particularly with reference to the pandemic.To determine the equity and potential benefits of implementation of the ReSPECT form process in BNSSG and contribute to the ACP evidence base, this study will describe the characteristics of patients in the BNSSG area who had a completed ReSPECT form recorded in their primary care medical records before, during and after the first wave of the COVID-19 pandemic; describe the content of ReSPECT forms; and analyse outcomes for those patients who died with a ReSPECT form.Methods and analysis We will perform an observational retrospective study on data, collected from October 2019 for 12 months. Data will be exported from the CCG Public Health Management data resource, a pseudonymised database linking data from organisations providing health and social care to people across BNSSG. Descriptive statistics of sociodemographic and health-related variables for those who completed the ReSPECT process with a clinician and had a documented ReSPECT form in their notes, in addition to their ReSPECT form responses, will be compared between before, during and after first COVID-19 wave groups. Additionally, routinely collected outcomes for patients who died in our study period will be compared between those who completed the ReSPECT process with a community clinician, hospital clinician or not at all. These include emergency department attendances, emergency hospital admissions, community nurse home visits, hospice referrals, anticipatory medication prescribing, place of death and if the patient died in preferred place of death.Ethics and dissemination Approval has been obtained from a National Health Service Research Ethics Committee (20/YH/0185). Findings will be disseminated to policy decision-makers, care providers and the public through scientific meetings and peer-reviewed publication.